1969
DOI: 10.1063/1.1652930
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Generation and Submillimeter Wave Mixing With the Josephson Effect

Abstract: By observing constant-voltage steps from Josephson junctions at voltages as high as 17 mV we deduce that junctions can generate harmonics up to frequencies as high as 8200 GHz. In consonance with this, submillimeter wave laser detection, harmonic generation, and mixing are demonstrated. These results suggest a model for the upper frequency limit of the Josephson effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

1970
1970
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 7 publications
0
10
0
4
Order By: Relevance
“…See also [54]. (23) In these works and also in our experiments with the conversion of 4 mm signal to X-band range the combination frequency oscillations were observed directly in contrast to the works [73], [85] where only the steps at the i-v curve corresponding to combination frequency were observed. See also [90].…”
Section: A9) Andmentioning
confidence: 41%
See 1 more Smart Citation
“…See also [54]. (23) In these works and also in our experiments with the conversion of 4 mm signal to X-band range the combination frequency oscillations were observed directly in contrast to the works [73], [85] where only the steps at the i-v curve corresponding to combination frequency were observed. See also [90].…”
Section: A9) Andmentioning
confidence: 41%
“…They were observed many many times at voltages up to 15 mV (n = 103) [85] and at frequencies up to 2.5 THz [86]. The dependence (ll)max on 03A9 is also shown at figure 13 by dashed line.…”
Section: A9) Andmentioning
confidence: 84%
“…McDonald et al, 19 have observed steps with point contacts at voltages well above the energy gap voltage. They show the steps produced by a 70-GHz irradiation to go at least to 17 m V (or 103rd step).…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Des études sont en cours [27,70,77] pour déterminer la fréquence ultime d'utilisation d'une jonction Josephson, qui peut être limitée par la capacité de la jonction, de l'ordre de 1 O -13 F, et par des effets thermiques dus aux niveaux de puissance injectée. D'autres études portent sur le niveau de puissance obtenu en fréquence intermédiaire, qui varie en N -2, N étant le facteur de multiplication utilisé.…”
Section: 1 2 La Diode Métal-isolant-métal(mim)unclassified
“…Pour r % 0,1 les lasers CO2 et HCN présentent un bruit flicker de fréquence (variation de l'écart-type des fluctuations de fréquence en r°) et pour i > 0,1 s (laser CO2) et r > 1 s (laser HCN), une dérive de fréquence due essentiellement à des effets thermiques et aux variations de courant de la décharge. Le laser CH30H (70,5 pm) a un bruit blanc de fréquence, dont l'écart-type des fluctuations de fréquence varie comme T -1/2 pour r % 0,1 s. Pour 0,1 s r K 1 s, le laser CH30H présente une dérive de fréquence.…”
unclassified